2020
DOI: 10.3389/fgene.2020.591667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RNA Binding Proteins on the Prognosis and Malignant Progression in Prostate Cancer

Abstract: Prostate cancer (PCa) is a common lethal malignancy in men. RNA binding proteins (RBPs) have been proven to regulate the biological processes of various tumors, but their roles in PCa remain less defined. In the present study, we used bioinformatics analysis to identify RBP genes with prognostic and diagnostic values. A total of 59 differentially expressed RBPs in PCa were obtained, comprising 28 upregulated and 31 downregulated RBP genes, which may play important roles in PCa. Functional enrichment analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…SDF2L1 is an independent prognostic indicator in breast cancer, and the reduced level of SDF2L1 is related to poor clinical outcomes ( Jiang et al, 2009 ). Two signatures of RNA-binding proteins enrolled the CTU1 gene as a vital indicator to predict the survival of prostate cancer and bladder urothelial carcinoma ( Guo et al, 2020 ; Hua et al, 2020 ). However, the effects of these 10 genes in NBL have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…SDF2L1 is an independent prognostic indicator in breast cancer, and the reduced level of SDF2L1 is related to poor clinical outcomes ( Jiang et al, 2009 ). Two signatures of RNA-binding proteins enrolled the CTU1 gene as a vital indicator to predict the survival of prostate cancer and bladder urothelial carcinoma ( Guo et al, 2020 ; Hua et al, 2020 ). However, the effects of these 10 genes in NBL have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Ming Zhang et al identi ed the copy number ampli cations of CTU1 in 25% of myxopapillary ependymomas by means of whole exome sequencing [43]. CTU1 has been identi ed as one of prognostic predictors for prostate cancer and bladder cancer [44,45]. We also identi ed NUFIP1 as a risk factor of CC patients.…”
Section: Discussionmentioning
confidence: 85%
“…REXO2 is a RNA binding protein and is required for maintaining the integrity of mitochondria 44 , 45 . Previous reports showed that higher expression levels of REXO2 were associated with the poor prognosis of prostate cancer 46 . However, the expression and prognosis of REXO2 in other malignant disease, particular in glioma were unknown.…”
Section: Discussionmentioning
confidence: 90%